A caroticocavernous fistula without vascular injury following endoscopic transsphenoidal excision of a tuberculum sellae meningioma—A case report - Jesse Zen, Ngui; George, Higginbotha; Davendran, Kanesen; Lau, Jia Him; Tang, Ing Ping; Donald N., S. Liew (John Wiley & Sons, Ltd., 2021)
Caroticocavernous fistulae can occur following transsphenoidal surgery even without evidence of carotid artery injury. A role of vascularized flap reconstruction may be contributory.